Effect of Boiling Time on the Utilization of Cocoa Bean Shell in Laying Hen Feeds - Olubamiwa, O.; Ikyo, S.M.; Adebowale, B.A.; Omojola, A.B.; Hamzat, R.A. (International Journal of Poultry Science, 2006)
Efficient utilization of cocoa by-products has been identified as one of the means of ensuring the sustainability of the cocoa economy. A series of studies was started in 2000 with the aim of finding commercial usage for cocoa bean shell (CBS) in poultry (layer) diets. In the first trial, CBS was fed raw at graded levels (0, 10, 20, 30 and 40%) of maize replacement in layers mash. Suffice it to mention that maize constitutes > 50% of most layer feeds. The 10% diet was significantly better (P< 0.05) utilized than others. The second study assessed variously treated CBS at the 10% level. The boiled and urea-treated CBS based rations were better (P< 0.05) utilized than others. The third trial, which used 20% dietary maize replacement by CBS, established the boiled (30-minutes) CBS to be superior (P< 0.05) to the urea-treated. The present investigation assessed the optimal boiling time for CBS among durations of 15, 30, 45 and 60 minutes. The 10-week experiment used one hundred and sixty-eight 32-weeks old laying hens. These were randomly allotted to the 7 treatments, which included 0% CBS diet, a commercial diet and an untreated CBS diet. The rest diets contained CBS boiled for 15, 20, 45 and 60 minutes. Maize was replaced at 20% level in the control mash in all the CBS based mashes. Among the CBS diets, only the 15-minutes boiled batch supported similar egg production and feed conversion as the Control diet. Feed intake and egg quality parameters were equal across treatments. Feed cost/kg egg was least on the 15-minutes boiled CBS diet.The results of this experiment indicated very strongly that the 15-minutes boiling duration is the best for optimal and profitable utilization of CBS in layers mash.